Respuesta :

EyeSpy
The zeros of a quadratic equation are equal to the x-intercepts of its graph. In other words, you must find the x-value that causes the expression to equal zero. Start by adding 4 to both sides of the equation:

X² - 5x + 4 = 0

Factor the equation:

(x - 1)(x - 4) = 0

Now calculate each piece separately, starting with the first one:

x - 1 = 0

Add 1 to both sides of the equation:

x = 1

We have proven that x = 1. Now calculate the second piece:

x - 4 = 0

Add 4 to both sides of the equation:

x = 4

We have proven that x = 4. Consequently, we have proven that (x = 1) and (x = 4) are the two zeros of this quadratic equation.

I hope this helps!